Effects of happy sensation training group on the symptom of anxiety, depression and sleep structure: a randomized controlled trial - Yan, Deping; Wang, Yunqiong; Li, Jia; Wang, Ling; Yao, Yongping; Deng, Jing (Frontiers in Neuroscience, 2025)
BackgroundNon-drug therapy is a common clinical treatment for chronic insomnia, and the effect of happiness perception training group based on five senses therapy on chronic insomnia has not been evaluated.ObjectiveThis study investigated the effects of happy sensation training group on anxiety, depression and insomnia symptoms in patients with chronic insomnia disorder.MethodsA prospective, assessor-blind, randomized controlled design was used. Adult patients with chronic insomnia were recruited from the Sleep Medicine Center of Sichuan Provincial Center for Mental Health. Participants in the training group received 10 sessions of hospital-based happy sensation training group therapy and three months of home exercises. The control group received health instruction. Results included anxiety, depression, and insomnia and were assessed at baseline, 2-week intervention, and 3-month follow-up. Polysomnography was performed at baseline and 2-week intervention. Two-way repeated measure ANOVA and Nonparametric test were used for data analysis.Results42 patients in the training group and 43 patients in the control group accomplished 3-month follow-up. There was no significant difference in anxiety, depression, insomnia and sleep Characteristics between training group and control group at baseline (P > 0.05). Compared with the control group, anxiety, depression and insomnia were improved in the training group after 2 weeks and at the 3-month follow-up (P < 0.05), sleep latency was shortened (P < 0.001), and sleep efficiency, total sleep time and N2 phase sleep were increased (P < 0.05).ConclusionHappiness sensation training group can effectively improve the anxiety and depression of chronic insomnia patients, so as to improve insomnia. Given its acceptability and practicality, the program could be incorporated into routine treatment.Clinical trial registrationhttps://www.chictr.org.cn/bin/project/edit?pid=210919, identifier ChiCTR2400082199.